2013
DOI: 10.1021/cg4003143
|View full text |Cite
|
Sign up to set email alerts
|

Growth Kinetics of the {10.4} Faces of Nitratine (NaNO3)

Abstract: Abstract.In this paper we focus on the measurement of the normal growth rates (R 104 ) of 10.4 faces of nitratine (NaNO 3 ) single crystals under isothermal conditions in the temperature interval 288  297. 5K in order to unravel the rate determining steps during crystal growth, depending on the hydrodynamic conditions. Owing to the elevated solubility of nitratine in water, the supersaturated system is very sensitive to temperature variation. In this sense we have constructed a device to control the tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The growth habit and morphology of crystal depends on the relative growth rate of different faces of crystal [20][21][22]. Fig.5a shows a schematic diagram of Sample 1#…”
Section: Growth Mechanismmentioning
confidence: 99%
“…The growth habit and morphology of crystal depends on the relative growth rate of different faces of crystal [20][21][22]. Fig.5a shows a schematic diagram of Sample 1#…”
Section: Growth Mechanismmentioning
confidence: 99%
“…[12][13][14] As calcite and II-NaNO 3 are isostructural we decided to try lithium carbonate as modifier of sodium nitrate morphology. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 7 For crystal growth measurements we used the device built for measuring the pure NaNO 3 growth rate described elsewhere, 15 while here we added different amounts of KNO 3 or LiNO 3 as impurities to determine the variation in the advancement rate of the crystal faces.…”
Section: ) Materials and Methodsmentioning
confidence: 99%
“…A valuable study on the growth behavior of sodium nitrate crystals was reported by Benages-Vilau et al 26 , though they only examined growth rates of NaNO3 (104) With up to 5 captured frames per second, the system can meet the needs of general crystal growth measurement. To achieve an accurate measurement requires that at least certain number of, say, 5 frames were captured during the whole growing process.…”
Section: Previous Workmentioning
confidence: 99%
“…Benages-Vilau et al 26 also glued the seed crystal on a sample holder with roughly the same solution velocity. The growth rate data obtained is coincident with this study in magnitude, but the supersaturation range studied is below 0.01.…”
Section: Comparison With Growth Rate Data From Literaturementioning
confidence: 99%